Penerapan Metode Struktural Analitik Sintetik (SAS) terhadap Kemampuan Membaca Permulaan Siswa Kelas I SD Negeri 11 Kodeoha Kabupaten Kolaka Utara - Nur Indah Mustaring; Andi Adam; Desy Ayu Andhira (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The problem in this research is whether the application of the Synthetic Structural Analytical (SAS) method can improve the initial reading ability of class I students at SD Negeri 11 Kodeoha, North Kolaka Regency. Meanwhile, the aim of the research carried out was to determine whether the application of the Synthetic Structural Analytical (SAS) method could improve the reading ability of beginners in class I of SD Negeri 11 Kodeoha, North Kolaka Regency. This type of research is pre-experimental research with a quantitative approach. The sample in this study was 22 class I students at SD Negeri 11 Kodeoha, North Kolaka Regency. The results of the research showed that there was an influence of the application of the Synthetic Analytical Structural (SAS) method on the initial reading ability of class I students at SD Negeri 11 Kodeoha, North Kolaka Regency. This can be seen from the comparison between the pre-test and post-test scores. The average pretest value obtained was 55.47. The average value was in the interval 55-64 which was included in the low category. Meanwhile, the average posttest score obtained was 81.94, which was in the 75-84 interval, which means it was in the high category. The research results obtained were tcount = 15.26 and ttable = 3.819. Then tCount ≥ tTable or 15.26 ≥ 3.819. So it can be concluded that Ho is rejected and H1 is accepted. This means that the application of the synthetic analytical structural method (SAS) can have an influence in improving the initial reading ability of class I students at SD Negeri 11 Kodeoha, Bulukumba Regency.